ECONOMIC EFFICIENCY OF SOCIAL ADVERTISING AND ITS DIFFERENCE FROM COMMERCIAL ADVERTISING (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article provides a comparative analysis of the similarities and differences between commercial and social advertising. The study substantiates the commonality of distribution channels of both types of advertising (SMI, outdoor advertising, New media, etc.). It also reveals the differences between the informational, economic, educational and social functions of advertising. Particular emphasis is placed on the strategic role of social advertising in ensuring the well-being of society and the long-term economic stability of the state.